(untitled) (Revista científica Olimpia, 2020)
This article presents the research carried out to contribute to the solution of the problem that exists in relation to the care of a patient suffering from Tetralogy of Fallot who has not yet undergone surgery, which is aggravated by his paraplegic condition as a result of this cardiac complication, with such notable consequences as lack of sensation in the lower extremities and muscle weakness. There are few known physical activity related alternatives to rehabilitate this type of patient. In view of this situation, the authors of the work have carried out research to answer the following problem: How to contribute to the community therapeutic physical rehabilitation of a paraplegic patient with Tetralogy of Fallot in the North Popular Council of the municipality of Urbano Noris? To this end, the objective has been to draw up a community therapeutic physical exercise program to contribute to the rehabilitation of a paraplegic patient with Tetralogy of Fallot for his return to an active social life. The selected sample coincides with the population; He is a young adult of 34 years of age of white race, resident in the North Popular Council of the Urbano Noris municipality, Holguín province, Cuba, who lives with a brother, orphaned by a mother who helped him in everything, so for these and other reasons his self-validity should be stimulated. For all these reasons, the investigation is important and pertinent.